Pengembangan Aplikasi Penjualan Pakaian Berbasis Android - Sarifudin, Riyan; Aryanto, Joko (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Online buying and selling (e-commerce) is one of the fastest-growing businesses that offers various conveniences. Ease for consumers in buying and selling transactions that can be done anytime, anywhere. The development of ecommerce in Indonesia is marked by the increasing number of e-commerce. Currently, there are still many clothing buying and selling businesses that still use manual methods in the buying and selling process, namely the buying and selling transaction data has not followed the transaction process like e-commerce that is developing at this time, such as payment and product selection is still manual so that consumers in making transactions are not given good service by the seller. So it is necessary to build an application system that can improve services and ease of transactions, in this case, building an online android-based e-commerce application with the aim of helping in the buying and selling transaction process so that it is easier like a growing online business today. Tests that have been carried out in applications help in the transaction process, and product data is loaded in the form of catalogs, sales, payments, payment verification, and receipt input can be done in the application. Admins input products in the application as a catalog and process consumer orders in the application, and consumers can make transactions like other ecommerce in the application.